Addressing Lake Beseka's challenges: Potential solutions - Hettiarachchi, Upeksha (International Food Policy Research Institute, 2023)
Lake Beseka, a shallow saline lake in the East African Rift Valley of Ethiopia, has expanded considerably since the 1960s, inundating a large land area. The lake’s expansion is a result of groundwater discharge, inflow from hot springs, and excess irrigation water entering the lake through subsurface flows